WAYS OF DEVELOPING A GREEN ECONOMY IN THE KYRGYZSTAN - Kydykbaeva E. K.; Sheveleva O. V. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The article reveals the essence of the "green" economy. Every year mankind has to think more and more often about the path along which it is going. Since the beginning of the industrial revolution in the world, a person has not thought about the harm his activities cause to the environment. People just didn't know about it. However, ignorance of the laws of the environment does not absolve humanity from the responsibility it bears towards future generations. The Industrial Revolution gave birth to the economic model of development that people use to this day. Of course, this model is effective, but after all, it has existed for more than a dozen years, and as we can see, it causes great damage to the environment. This model is called the "brown economy" To solve problems with the environment, it is necessary to use the work of greening nature. The directions of development of the "green" economy are considered. Participation in the implementation of the Green Economy Concept of Kyrgyzstan.